Report of the Working Group on Machine Building Transport Equipment and Allied Industries Eighth Five Year Plan - Planning Commission (Planning Commission, 1990)
The Working Groups held a number of meetings to consider the report submitted by the different Sub-Groups. Reference was also made to the reports of the Advisory Groups on Capital goods Industry constituted by Planning Commission in Nov,1985 as also to the report of the Expert Group on Modernisation, Technology Upgradation and Accelerated Growth of the Industrial Machinery Industry set up subsequently by the Planning Commission in March, 1987 under the chairmanship of Sh. Mantosh Sondhi. The above reports deal comprehensively with various aspects of capital goods industry/sector including the industrial machinery sector.
Ministry of Industry Government of India
Ministry of Industry Government of India